2011
DOI: 10.2355/isijinternational.51.1044
|View full text |Cite
|
Sign up to set email alerts
|

Addition Effect of Model Compounds of Coal Extract on Coke Strength

Abstract: Eight polyaromatic hydrocarbons that are model compounds of coal extract were added to coal blends to clarify the mechanism of the effects of coal extract (HyperCoal) on coke strength. Addition of large aromatic-ring compounds (coronene, perylene, naphtho[2,3-a]pyrene) greatly enhanced coke strength, whereas three-ring aromatics (anthracene, phenanthrene) had no significant effect on coke strength. Because large polyaromatic compounds have greater affinity for coal molecules, they co-fused with the coal partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…To overcome the problem of decrease in coke strength, there has been recent interest in using oil/coal derived additives as binders so that the coke strength is maintained even with increased low quality non-caking coals addition. [3][4][5][6] Takanohashi et al explained this increase in coke strength by investigating the interaction between caking and slightly caking or non-caking coals using NMR analysis and H/C ratio and concluded that binders (HPC) enhance the thermoplasticity of the coal blend due to their high thermoplasticity and overlapping thermoplastic temperature range with that of base coals. 4) Sakimoto et al introduced carbon matrix connectivity index to estimate the coke drum index which directly correlates with the coke strength.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the problem of decrease in coke strength, there has been recent interest in using oil/coal derived additives as binders so that the coke strength is maintained even with increased low quality non-caking coals addition. [3][4][5][6] Takanohashi et al explained this increase in coke strength by investigating the interaction between caking and slightly caking or non-caking coals using NMR analysis and H/C ratio and concluded that binders (HPC) enhance the thermoplasticity of the coal blend due to their high thermoplasticity and overlapping thermoplastic temperature range with that of base coals. 4) Sakimoto et al introduced carbon matrix connectivity index to estimate the coke drum index which directly correlates with the coke strength.…”
Section: Introductionmentioning
confidence: 99%
“…The soluble fraction contained THF, 1-MN solvent and 1-MN soluble coal fraction. 3,6,9,19,20,[25][26][27]32) As can be seen from the Fig. 1, in the case of THF wash approach, 1-MN soluble coal fraction and insoluble fraction are separated.…”
Section: Methodsmentioning
confidence: 89%
“…Another approach is to chemical upgrade the coal by increasing its H/C ratio by solvent treatment. [3][4][5][6][7][8][9][10][11][20][21][22][23][24][25] Takanohashi et al treated different coals with 1-MN and obtained 1-MN soluble fractions. 7,32) This 1-MN soluble coal fraction was called coal-derived binder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Koyano et al investigated the effect of the aromatic ring size of model compounds added to coals on the coke strength of blended coals, and reported that the coke strength was increased by adding more than 4 aromatic rings and the effect was enhanced with increase in the number of aromatic rings. 12) Sakimoto et al also reported that the aromatic ring size of HPCs obtained from the extraction of low-rank coals with 1-methyl naphthalene at 673 K was around 3, although the extraction yield was 20-26 mass%, daf. 9) In the present study, in order to utilize low-rank coals efficiently, polar solvents were used as an extraction solvent, because a higher extraction yield can be expected.…”
Section: Introductionmentioning
confidence: 99%